PARS PLANA VITRECTOMY IN ADVANCED CASES OF VON HIPPEL–LINDAU EYE DISEASE. Issue 2 (February 2016) - Krzystolik, Karol; Stopa, Marcin; Kuprjanowicz, Leszek; Drobek-Slowik, Monika; Cybulski, Cezary; Jakubowska, Anna; Gronwald, Jacek; Lubiński, Jan; Lubiński, Wojciech
Abstract : Purpose: To investigate spectrum of patients with Von Hippel–Lindau disease (VHL) that required pars plana vitrectomy and evaluate anatomical and functional outcomes of surgery. Methods: Twenty-three patients who underwent surgery for advanced VHL eye disease were assessed by genetic tests, diagnostic tests for systemic lesions, and clinical eye examination. The vitrectomized eyes were divided into two groups: with or without retinotomy (group R vs. NR). Functional and anatomical outcome was analyzed and compared between the groups. Results: All patients had central nervous system hemangioblastomas and 57% had other systemic tumors. Point germline mutations, large partial deletions, and complete vhl gene deletions were found in 64%, 27%, and 9% of patients, accordingly. Destruction of hemangioblastomas by retinotomy, laser, or cryotherapy and anatomical attachment of the retina were achieved in all eyes. Preoperative mean distance best-corrected visual acuity was logarithm of the minimum angle of resolution 2.66 (20/9, 140) in group R and 1.76 (20/1, 150) in group NR ( P < 0.05). At 6 months postoperatively, distance best-corrected visual acuity improved in 20 eyes (83%). After over 24 months postoperatively, distance best-corrected visual acuity remained better than preoperatively in 36% in the R group and in 70% in the NR group of eyes. During 24 months postoperatively in 17 eyes, new retinal capillary hemangiomas developed. The mean number of new retinal capillary hemangiomas per eye was higher in group R than in group NR (3.14 vs. 0.70; P < 0.01). In group R, number of new retinal capillary hemangioblastoma was higher in retinal segments where retinotomy was performed (n = 29) than in other areas (n = 13) ( P < 0.01). Conclusion: Advanced VHL eye disease correlates with occurrence of central nervous system and systemic lesions. Spectrum of vhl gene mutation in the patients corresponds to that of the general VHL population. Pars plana vitrectomy in advanced VHL eye disease can improve or preserve visual function, but postoperative progression of ocular VHL disease can be accelerated in cases where retinotomy is performed. Abstract : The study presents spectrum of patients with Von Hippel–Lindau disease and advanced eye disease that required pars plana vitrectomy and evaluates anatomical and functional outcomes of surgery.